Techno-Socio-Economic Dimensions of Specialized Home Gardens - Sreelakshmi, C; Thomas, Allan (Journal of Extension Education, 2019)
The paper on home gardens delineates the techno-socio-economic dimensions of specializations in home gardens involving a total of 90 respondents from Thiruvanthapuram district in Kerala that comprised 60 specialized home garden farmers and 30 Agricultural Officers. Commercial interest has transformed this subsistence production system, to a means of additional income generation system with the inclusion of various specializations such as aquaculture, floriculture, sericulture and animal husbandry thus making it unique, ever-evolving and dynamic system. Different techno-socio- economic dimensions would have contributed to specializations in home gardens and hence the study was imperative. The results revealed that 11 out of 27 dimensions were perceived to be important. The results also revealed that the relevancy pattern differed for both specialized home garden farmers and agricultural officers wherein a few dimensions perceived to be important by farmers were actually not a concern for agricultural officers and vice versa.